Photocatalyst and preparation method thereof
By developing a photocatalyst composed of fly ash-based molecular sieve and TiO2 photocatalysts supported thereon, the problem of high cost of preparation of existing photocatalysts is solved, and efficient treatment of dye wastewater and effective utilization of resources are achieved.
Patent Information
- Application Number
- CN202411706907.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-28
AI Technical Summary
The existing photocatalysts are costly to purify and treat dye wastewater, and it is difficult to effectively utilize fly ash and nanoTiO2.
A photocatalyst is developed, which consists of a fly ash-based molecular sieve and a TiO2 photocatalyst supported in a fly ash-based molecular sieve. The TiO2 photocatalyst is supported on the fly ash-based molecular sieve by a specific preparation method to form a photocatalyst with a high specific surface area and porosity.
The photocatalyst preparation cost is reduced, and its selective adsorption performance and catalytic effect on small molecule substances are improved. Especially when treating methyl orange wastewater solution, it shows outstanding degradation effect, and the photocatalyst can be regenerated and recycled repeatedly.
Smart Images

Figure CN119702049A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photocatalytic materials, and in particular to a photocatalyst and a preparation method thereof. Background Art
[0002] With the rapid development of modern industry, the problem of ecological pollution is becoming increasingly serious. Among all kinds of pollution, water pollution is the most serious problem that harms human life. There are many reasons for water pollution, mainly because the pollutants have complex components, large emissions, high COD content and unstable water quality. Among them, dye wastewater is a kind of industrial wastewater that is difficult to treat. The dyes in the wastewater will absorb the light radiated by the sun, thereby reducing the transparency of the water body itself, resulting in a large-scale consumption of oxygen in the water, which will not only cause serious hypoxia in the water body and affect the organisms in the water body, but also reduce its own purification ability. In addition, water resources in nature are mobile. The harmful dyes in the wastewater will flow into rivers through the drainage system with the water body, and will penetrate the surface and infiltrate into the groundwater, causing long-term damage to the environment and affecting human health.
[0003] In addition, fly ash, as a kind of solid waste, has a high output but a low utilization rate. If it is stored, it will cause a waste of land resources. Nano-TiO2 has excellent photocatalytic properties, but it is difficult to immobilize and recycle. At present, it is urgent to develop a photocatalyst that can comprehensively utilize fly ash and nano-TiO2 and can be effectively used for the purification of large-scale dye wastewater. Summary of the invention
[0004] The main purpose of the present invention is to provide a photocatalyst and a preparation method thereof, so as to solve the problem of high preparation cost of the photocatalyst used for purifying dye wastewater in the prior art.
[0005] In order to achieve the above object, according to one aspect of the present invention, a photocatalyst is provided, which comprises a fly ash-based molecular sieve and a TiO2 photocatalyst loaded in the fly ash-based molecular sieve, wherein the specific surface area of the photocatalyst is 30 to 70 m 2 / g, and the porosity of the photocatalyst is 40-80%.
[0006] Furthermore, the mass ratio of the above-mentioned fly ash-based molecular sieve to TiO2 photocatalyst is 1:3~3:1, preferably 1:2~1:1, and / or the fly ash-based molecular sieve is selected from any one or more of fly ash-based MCM-41 molecular sieve, fly ash-based 4A molecular sieve, and fly ash-based NaY molecular sieve.
[0007] Furthermore, the average particle size of the photocatalyst is 2 to 50 nm.
[0008] According to one aspect of the present invention, there is provided a method for preparing the above-mentioned photocatalyst, which comprises: step S1, performing a first mixing of raw materials including a titanium source and a first solvent and then standing the mixture to obtain a sol-gel; step S2, performing a first drying and a first calcination on the sol-gel in sequence to obtain a TiO2 photocatalyst; step S3, performing a second mixing of raw materials including a fly ash-based molecular sieve, a TiO2 photocatalyst and a second solvent and then performing a second drying and a second calcination in sequence to obtain a photocatalyst.
[0009] Furthermore, in the above step S1, the titanium source is butyl phthalate and / or titanium tetrachloride, and the mass ratio of the titanium source to the fly ash-based molecular sieve is 1-3.12:1-3.
[0010] Furthermore, in the above step S1, the mass ratio of the fly ash-based molecular sieve to the volume ratio of the first solvent is 0.0128 to 0.018 g / mL; and / or, the mass ratio of the titanium source to the volume ratio of the first solvent is 0.03 to 0.042 g / mL; and / or, the first solvent is a mixed solvent of an alcohol solvent and water, preferably, the volume ratio of the alcohol solvent to water is 4 to 4.75:1, and the alcohol solvent is preferably ethanol and / or methanol.
[0011] Furthermore, in the above step S1, the temperature of the first mixing is 25 to 30° C.; and / or the standing time is 12 to 24 hours.
[0012] Furthermore, in the above step S2, the first drying temperature is 70-100°C, and the first drying time is 6-8h; and / or, the first calcination is performed at a heating rate of 5-7°C / min, and / or, the first calcination temperature is 550-600°C, and / or, the first calcination time is 3-4h.
[0013] Furthermore, in the above step S3, the average particle size of the fly ash-based molecular sieve is 20 to 200 meshes; and / or the second solvent is selected from any one or more of anhydrous ethanol, methanol, and methylcyclohexane; and / or the second mixing process includes ultrasonic dispersion and magnetic stirring performed in sequence, and the ultrasonic dispersion time is 30 to 45 minutes; and / or the ultrasonic dispersion frequency is 40 to 50 kHz; and / or the magnetic stirring time is 4 to 5 hours, and / or the magnetic stirring speed is 100 to 700 rpm, and / or the temperatures of ultrasonic dispersion and magnetic stirring are each independently 20 to 30°C.
[0014] Furthermore, in the above step S3, the second drying temperature is 70-80°C, and / or the second drying time is 4-5h; and / or the second calcination is performed at a heating rate of 5-7°C / min, and / or the second calcination temperature is 400-450°C, and / or the second calcination time is 2-3.5h.
[0015] By applying the technical solution of the present invention, the photocatalyst of the present application utilizes the uniform pore structure in the fly ash-based molecular sieve on the one hand, combined with the excellent photocatalytic performance of the TiO2 photocatalyst, so that the photocatalyst has the above specific surface area and porosity, thereby better improving its selective adsorption performance for small molecules. On the other hand, the photocatalyst of the present application utilizes the transition metals in the fly ash-based molecular sieve, and improves its catalytic effect on molecules through its synergistic effect with the TiO2 photocatalyst. Through the above two effects, the photocatalyst of the present application has a better catalytic effect, and the photocatalyst is used for industrial wastewater treatment, especially the degradation effect of methyl orange wastewater solution is outstanding. In addition, the fly ash-based molecular sieve in the photocatalyst of the present application is widely available, low-priced, belongs to waste utilization, has no secondary pollution, and greatly reduces the preparation cost of the photocatalyst. And the photocatalytic adsorbent of the present application can be repeatedly regenerated and recycled, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0017] Figure 1 The process flow chart of preparing the photocatalyst in Example 1 of the present application is shown;
[0018] Figure 2 The graph shows the degradation rate of methyl orange wastewater by photocatalysis in Examples 1 to 5 of the present application. DETAILED DESCRIPTION
[0019] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0020] As analyzed in the background technology of the present application, there is a problem in the prior art that the preparation cost of photocatalysts used for purifying dye wastewater is high. In order to solve the above problem, the present application provides a photocatalyst and a preparation method thereof.
[0021] In a typical embodiment of the present application, a photocatalyst is provided, which includes a fly ash-based molecular sieve and a TiO2 photocatalyst loaded in the fly ash-based molecular sieve, and the specific surface area of the photocatalyst is 30 to 70 m 2 / g, and the porosity of the photocatalyst is 40-80%.
[0022] On the one hand, the photocatalyst of the present application utilizes the uniform pore structure in the fly ash-based molecular sieve, combined with the excellent photocatalytic performance of the TiO2 photocatalyst, so that the photocatalyst has the above specific surface area and porosity, thereby better improving its selective adsorption performance for small molecules. On the other hand, the photocatalyst of the present application utilizes the transition metals in the fly ash-based molecular sieve, and improves its catalytic effect on molecules through its synergistic effect with the TiO2 photocatalyst. Through the above two effects, the photocatalyst of the present application has a better catalytic effect, and the photocatalyst is used for industrial wastewater treatment, especially the degradation effect of methyl orange wastewater solution is outstanding. In addition, the fly ash-based molecular sieve in the photocatalyst of the present application is widely available, low-priced, belongs to waste utilization, has no secondary pollution, and greatly reduces the preparation cost of the photocatalyst. And the photocatalytic adsorbent of the present application can be repeatedly regenerated and recycled, and has broad application prospects.
[0023] In one embodiment of the present application, the mass ratio of the above-mentioned fly ash-based molecular sieve to TiO2 photocatalyst is 1:3~3:1, preferably 1:2~1:1, and / or the fly ash-based molecular sieve is selected from any one or more of fly ash-based MCM-41 molecular sieve, fly ash-based 4A molecular sieve, and fly ash-based NaY molecular sieve.
[0024] The preferred mass ratio of the fly ash-based molecular sieve to the TiO2 photocatalyst is more helpful to improve the overall catalytic effect of the photocatalyst. The preferred fly ash-based molecular sieve further improves the rich pore structure of the photocatalyst.
[0025] In one embodiment of the present application, the average particle size of the photocatalyst is 2 to 50 nm.
[0026] The photocatalyst having the above average particle size has a suitable specific surface area, so that the photocatalyst is not easy to agglomerate and has a large specific surface area, thereby increasing its contact area with the wastewater and further improving the catalyst's treatment effect on wastewater.
[0027] In a typical embodiment of the present application, a method for preparing the above-mentioned photocatalyst is provided, and the preparation method comprises: step S1, performing a first mixing of raw materials including a titanium source and a first solvent and then standing the mixture to obtain a sol-gel; step S2, performing a first drying and a first calcination on the sol-gel in sequence to obtain a TiO2 photocatalyst; step S3, performing a second mixing of raw materials including a fly ash-based molecular sieve, a TiO2 photocatalyst, and a second solvent and then performing a second drying and a second calcination in sequence to obtain a photocatalyst.
[0028] Nano-TiO2 has excellent photocatalytic performance, but it is difficult to immobilize and recycle, while fly ash-based molecular sieve has a uniform pore structure and has excellent selective adsorption performance for small molecules. The above preparation method of the present application uses fly ash-based molecular sieve as the basic carrier, and successfully loads TiO2 photocatalyst on fly ash-based molecular sieve. The above preparation process is simple and the raw material source is wide. And the photocatalyst of the present application, on the one hand, utilizes the uniform pore structure in the fly ash-based molecular sieve, combined with the excellent photocatalytic performance of TiO2 photocatalyst, so that the photocatalyst has the above specific surface area and porosity, thereby better improving its selective adsorption performance for small molecules. On the other hand, the photocatalyst of the present application utilizes the transition metal in the fly ash-based molecular sieve, and improves its catalytic effect on molecules through its synergistic effect with the TiO2 photocatalyst. Through the above two aspects, the photocatalyst of the present application has a better catalytic effect, and the photocatalyst is used for industrial wastewater treatment, and its degradation effect on methyl orange wastewater solution is particularly outstanding. In addition, the fly ash-based molecular sieve in the photocatalyst of the present application is widely available, inexpensive, and waste-recycling, without secondary pollution, which greatly reduces the preparation cost of the photocatalyst. Moreover, the photocatalytic adsorbent of the present application can be repeatedly regenerated and recycled, and has broad application prospects.
[0029] In one embodiment of the present application, in the above step S1, the titanium source is butyl phthalate and / or titanium tetrachloride, and the mass ratio of the titanium source to the fly ash-based molecular sieve is 1-3.12:1-3.
[0030] The above optimization of the titanium source type is more helpful to obtain the TiO2 photocatalyst after the above steps S1 and S2. The preferred mass ratio of the titanium source and the fly ash-based molecular sieve is helpful to control the mass ratio of the fly ash-based molecular sieve to the TiO2 photocatalyst in the photocatalyst within a certain range, thereby maximizing the catalytic performance of the catalyst.
[0031] In one embodiment of the present application, in the above step S1, the mass ratio of the fly ash-based molecular sieve to the volume ratio of the first solvent is 0.0128-0.018 g / mL; and / or, the mass ratio of the titanium source to the volume ratio of the first solvent is 0.03-0.042 g / mL; and / or, the first solvent is a mixed solvent of an alcohol solvent and water, preferably, the volume ratio of the alcohol solvent to water is 4-4.75:1, and the alcohol solvent is preferably ethanol and / or methanol.
[0032] The preferred usage ratio of the above titanium source and fly ash-based molecular sieve relative to the first solvent, and the preferred first solvent being the above types, are more helpful in improving the dispersion effect of the titanium source and fly ash-based molecular sieve in the first solvent, thereby improving the uniformity of the resulting sol-gel.
[0033] In order to improve the sol-gel formation efficiency, preferably, in the above step S1, the temperature of the first mixing is 25 to 30° C.; and / or the standing time is 12 to 24 hours.
[0034] In one embodiment of the present application, in the above step S2, the first drying temperature is 70-100°C, and the first drying time is 6-8h; and / or, the first calcination is performed at a heating rate of 5-7°C / min, and / or, the first calcination temperature is 550-600°C, and / or, the first calcination time is 3-4h.
[0035] The preferred first drying temperature and time are within the above ranges, which is conducive to improving the efficiency and effect of the first drying. The preferred first calcination temperature, time and heating rate are within the above ranges, which is conducive to improving the efficiency and effect of the first calcination as a whole and obtaining a TiO2 photocatalyst with excellent performance.
[0036] In one embodiment of the present application, in the above step S3, the average particle size of the fly ash-based molecular sieve is 20 to 200 mesh; and / or the second solvent is selected from any one or more of anhydrous ethanol, methanol, and methylcyclohexane; and / or the second mixing process includes ultrasonic dispersion and magnetic stirring performed in sequence, and the ultrasonic dispersion time is 30 to 45 minutes; and / or the ultrasonic dispersion frequency is 40 to 50 kHz; and / or the magnetic stirring time is 4 to 5 hours, and / or the magnetic stirring speed is 100 to 700 rpm, and / or the temperatures of ultrasonic dispersion and magnetic stirring are each independently 20 to 30°C.
[0037] The preferred average particle size of the fly ash-based molecular sieve is within the above range, which is more conducive to improving the synergistic coordination between the fly ash-based molecular sieve and the TiO2 photocatalyst, thereby better loading the TiO2 photocatalyst on the fly ash-based molecular sieve. Controlling the second mixing to the above process is more conducive to improving the dispersion uniformity of the fly ash-based molecular sieve and the TiO2 photocatalyst, thereby allowing the TiO2 photocatalyst to be more fully and evenly loaded on the fly ash-based molecular sieve.
[0038] In one embodiment of the present application, in the above step S3, the second drying temperature is 70-80°C, and / or the second drying time is 4-5h; and / or the second calcination is performed at a heating rate of 5-7°C / min, and / or the second calcination temperature is 400-450°C, and / or the second calcination time is 2-3.5h.
[0039] The preferred second drying temperature and time are within the above ranges, which is conducive to improving the efficiency and effect of the second drying. The preferred second calcination temperature, time and heating rate are within the above ranges, which is conducive to improving the efficiency and effect of the second calcination as a whole and obtaining a photocatalyst with excellent performance.
[0040] In addition, the preparation method of fly ash-based MCM-41 molecular sieve in this application is exemplified by taking the preparation method of fly ash-based MCM-41 molecular sieve as an example, as follows:
[0041] 1) Mix fly ash with a certain amount of 0.1-4.0 mol / L alkaline solution, stir and react at a certain temperature for a period of time, and filter to obtain a supernatant (solid content of 40-68%);
[0042] 2) Mixing the template with a certain proportion of water, stirring at a certain temperature until the solution becomes clear, and obtaining a template solution (mass concentration of 8-9.2%);
[0043] 3) At a certain temperature, slowly drop the clear liquid into the template solution, continue stirring after the addition is complete and adjust the pH to 8-9, and continue the reaction for a period of time to obtain a white gel solution;
[0044] 4) pouring the white gel solution into a hydrothermal reaction kettle, sealing it and placing it in an oven for crystallization at 90-120° C. to obtain a crystallized product;
[0045] 5) After the crystallized product is cooled and filtered, the template agent is extracted with an extractant and then washed to neutrality, the product is placed in an oven to dry, and then calcined in a muffle furnace to obtain MCM-41 molecular sieve powder.
[0046] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.
[0047] Example 1
[0048] according to Figure 1 The preparation process flow chart shown is used to prepare the photocatalyst:
[0049] 1) Preparation of titanium dioxide photocatalyst: 25 mL of tetrabutyl titanate, 25 mL of deionized water and 100 mL of anhydrous ethanol were first mixed and allowed to stand for 12 h to obtain a sol-gel; the sol-gel was dried in an oven at 100° C. for 4 h, and finally placed in a muffle furnace and calcined at 550° C. for 3 h to obtain a TiO2 photocatalyst.
[0050] 2) Preparation of photocatalyst: 0.64 g of 20-200 mesh fly ash-based MCM-41 powder was dissolved in 50 mL of anhydrous ethanol, mixed and stirred to form a mixed slurry, the mixed slurry was magnetically stirred for 4 h, and baked in an oven at 80°C for 4 h. The obtained molded product was transferred to a crucible and calcined at 400°C and 5°C / min for 2 h to obtain a photocatalyst. During the magnetic stirring process, TiO2 catalyst was added at a mass ratio of 1:2 between TiO2 photocatalyst and fly ash-based MCM-41.
[0051] Example 2
[0052] The difference from Example 1 is that the mass ratio of tetrabutyl titanate to fly ash-based MCM-41 is 1.04:1, and the mass ratio of fly ash-based MCM-41 to TiO2 photocatalyst is 1:1, and finally a TiO2 catalyst is obtained.
[0053] Example 3
[0054] The difference from Example 1 is that the mass ratio of tetrabutyl titanate to fly ash-based MCM-41 is 3.12:1, and the mass ratio of fly ash-based MCM-41 to TiO2 photocatalyst is 1:3, and finally a TiO2 catalyst is obtained.
[0055] Example 4
[0056] The difference from Example 1 is that the mass ratio of tetrabutyl titanate to fly ash-based MCM-41 is 1.04:2, and the mass ratio of fly ash-based MCM-41 to TiO2 photocatalyst is 2:1, and finally a TiO2 catalyst is obtained.
[0057] Example 5
[0058] The difference from Example 1 is that the mass ratio of tetrabutyl titanate to fly ash-based MCM-41 is 1.04:3, and the mass ratio of fly ash-based MCM-41 to TiO2 photocatalyst is 3:1, and finally a TiO2 catalyst is obtained.
[0059] Example 6
[0060] The difference from Example 1 is that 1) preparing titanium dioxide photocatalyst: 25 mL of tetrabutyl titanate, 25 mL of deionized water and 100 mL of anhydrous ethanol are first mixed and then allowed to stand for 18 hours to obtain a sol-gel; the sol-gel is placed in an oven at 100°C and dried for 6 hours, and finally placed in a muffle furnace and calcined at 550°C for 3 hours to obtain a TiO2 photocatalyst, and finally a TiO2 catalyst is obtained.
[0061] Example 7
[0062] The difference from Example 1 is that 1) preparing the photocatalyst titanium dioxide: 25 mL of tetrabutyl titanate, 25 mL of deionized water and 100 mL of anhydrous ethanol are first mixed and then allowed to stand for 24 hours to obtain a sol-gel; the sol-gel is placed in an oven at 70°C and dried for 6 hours, and finally placed in a muffle furnace and calcined at 600°C for 3 hours to obtain a TiO2 photocatalyst, and finally a TiO2 catalyst is obtained.
[0063] Example 8
[0064] The difference from Example 1 is that 2) preparing the photocatalyst: 0.64 g of 20-200 mesh fly ash-based MCM-41 powder was dissolved in 50 mL of anhydrous ethanol, mixed and stirred to form a mixed solution, the mixed solution was magnetically stirred for 4 h, and baked in an oven at 80°C for 4 h, the obtained molded product was transferred to a crucible, and roasted at 400°C and 5°C / min for 2 h to obtain a photocatalyst. During the magnetic stirring process, TiO2 catalyst was added at a mass ratio of 1:2 between TiO2 catalyst and fly ash-based MCM-41, and finally a TiO2 catalyst was obtained.
[0065] Example 9
[0066] The difference from Example 1 is that 2) preparing the photocatalyst: 0.64 g of 20-200 mesh fly ash-based MCM-41 powder was measured and dissolved in 50 mL of anhydrous ethanol, mixed and stirred to form a mixed solution, the mixed solution was stirred magnetically for 4 hours, and baked in an oven at 80°C for 4 hours, the obtained molded product was transferred to a crucible, and roasted at 450°C and 5°C / min for 2 hours to obtain a photocatalyst. During the magnetic stirring process, TiO2 catalyst was added at a mass ratio of 1:2 between TiO2 catalyst and fly ash-based MCM-41, and finally a TiO2 catalyst was obtained.
[0067] The degradation test of methyl orange by the titanium dioxide / fly ash-based MCM-41 composite material is as follows:
[0068] 0.125 g of the photocatalyst obtained in the above examples was weighed and added to 100 mL of a methyl orange solution with a concentration of 20 mg / L and a pH of 6.
[0069] The light source of this experiment is a 300W ultraviolet xenon lamp. Under ultraviolet light irradiation, stirring is carried out on a magnetic stirrer at room temperature for 2.5 hours. At the same time, the surface of the beaker is covered with plastic wrap to prevent the solution from splashing or evaporating and affecting the test results. The liquid after the reaction is centrifuged and the supernatant is taken out. Then, the ultraviolet visible spectrophotometer is used to measure and the concentration of methyl orange remaining in the supernatant is calculated by the methyl orange standard curve formula y=0.06983x+0.00878. The degradation rate of methyl orange in Examples 1 to 5 changes with time as shown in the following figure: Figure 2 As shown in the figure, it can be seen that the degradation rate of methyl orange gradually increases with the growth of time. In Example 1, when it reaches 0.5h, the degradation rate of methyl orange can reach 20.64%. When the cumulative reaction time is 2.5h, the removal rate of methyl orange can reach 80.79%, achieving the purpose of removing methyl orange. And when the mass ratio of TiO2 precursor to fly ash-based MCM-41 is 1:2, the degradation rate of methyl orange by the photocatalyst is the best.
[0070] In Examples 6 to 9, the degradation rates of methyl orange at 30 min, 60 min, 90 min, 120 min and 150 min are shown in Table 1.
[0071] Table 1
[0072]
[0073] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0074] On the one hand, the photocatalyst of the present application utilizes the uniform pore structure in the fly ash-based molecular sieve, combined with the excellent photocatalytic performance of the TiO2 photocatalyst, so that the photocatalyst has the above specific surface area and porosity, thereby better improving its selective adsorption performance for small molecules. On the other hand, the photocatalyst of the present application utilizes the transition metals in the fly ash-based molecular sieve, and improves its catalytic effect on molecules through its synergistic effect with the TiO2 photocatalyst. Through the above two effects, the photocatalyst of the present application has a better catalytic effect, and the photocatalyst is used for industrial wastewater treatment, especially the degradation effect of methyl orange wastewater solution is outstanding. In addition, the fly ash-based molecular sieve in the photocatalyst of the present application is widely available, low-priced, belongs to waste utilization, has no secondary pollution, and greatly reduces the preparation cost of the photocatalyst. And the photocatalytic adsorbent of the present application can be repeatedly regenerated and recycled, and has broad application prospects.
[0075] The above are only embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A photocatalyst, characterized in that: The photocatalyst comprises a fly ash-based molecular sieve and a TiO2 photocatalyst loaded in the fly ash-based molecular sieve, and the specific surface area of the photocatalyst is 30 to 70 m 2 / g, and the porosity of the photocatalyst is 40-80%.
2. The photocatalyst according to claim 1, characterized in that The mass ratio of the fly ash-based molecular sieve to the TiO2 photocatalyst is 1:3 to 3:1, preferably 1:2 to 1:1, and / or the fly ash-based molecular sieve is selected from any one or more of fly ash-based MCM-41 molecular sieve, fly ash-based 4A molecular sieve, and fly ash-based NaY molecular sieve.
3. The photocatalyst according to claim 1 or 2, characterized in that The average particle size of the photocatalyst is 2 to 50 nm.
4. A method for preparing the photocatalyst according to any one of claims 1 to 3, characterized in that: The preparation method comprises: Step S1, mixing raw materials including a titanium source and a first solvent and then standing to obtain a sol-gel; Step S2, sequentially performing a first drying and a first calcination on the sol-gel to obtain a TiO2 photocatalyst; Step S3, performing a second mixing on the raw materials including the fly ash-based molecular sieve, the TiO2 photocatalyst, and the second solvent, and then sequentially performing a second drying and a second calcination to obtain the photocatalyst.
5. The preparation method according to claim 4, characterized in that: In the step S1, the titanium source is butyl phthalate and / or titanium tetrachloride, and the mass ratio of the titanium source to the fly ash-based molecular sieve is 1-3.12:1-3.
6. The preparation method according to claim 4 or 5, characterized in that: In the step S1, the mass ratio of the fly ash-based molecular sieve to the volume ratio of the first solvent is 0.0128 to 0.018 g / mL; and / or the mass ratio of the titanium source to the volume ratio of the first solvent is 0.03 to 0.042 g / mL; and / or the first solvent is a mixed solvent of an alcohol solvent and water, preferably the volume ratio of the alcohol solvent to the water is 4 to 4.75:1, and preferably the alcohol solvent is ethanol and / or methanol.
7. The preparation method according to any one of claims 4 to 6, characterized in that: In the step S1, the temperature of the first mixing is 25 to 30° C.; and / or the standing time is 12 to 24 hours.
8. The preparation method according to any one of claims 4 to 7, characterized in that In the step S2, the first drying temperature is 70-100°C, and the first drying time is 6-8h; and / or the first calcination is performed at a heating rate of 5-7°C / min, and / or the first calcination temperature is 550-600°C, and / or the first calcination time is 3-4h.
9. The preparation method according to any one of claims 4 to 8, characterized in that: In step S3, the average particle size of the fly ash-based molecular sieve is 20-200 mesh; and / or, the second solvent is selected from any one or more of anhydrous ethanol, methanol, and methylcyclohexane; And / or the second mixing process includes ultrasonic dispersion and magnetic stirring performed in sequence, the ultrasonic dispersion time is 30 to 45 minutes; and / or the ultrasonic dispersion frequency is 40 to 50 kHz; and / or the magnetic stirring time is 4 to 5 hours, and / or the magnetic stirring speed is 100 to 700 rpm, and / or the temperatures of the ultrasonic dispersion and the magnetic stirring are each independently 20 to 30°C.
10. The preparation method according to any one of claims 4 to 9, characterized in that: In the step S3, the second drying temperature is 70-80°C, and / or the second drying time is 4-5h; and / or the second calcination is performed at a heating rate of 5-7°C / min, and / or the second calcination temperature is 400-450°C, and / or the second calcination time is 2-3.5h.